The epidemiology of cardiovascular disease in the UK 2014. Issue 15 (3rd June 2015) - Bhatnagar, Prachi; Wickramasinghe, Kremlin; Williams, Julianne; Rayner, Mike; Townsend, Nick
Abstract : Cardiovascular disease (CVD) presents a significant burden to the UK. This review presents data from nationally representative datasets to provide up-to-date statistics on mortality, prevalence, treatment and costs. Data focus on CVD as a whole, coronary heart disease (International Classification of Diseases (ICD):I20–25) and cerebrovascular disease (ICD:I60–69); however, where available, other cardiovascular conditions are also presented. In 2012, CVD was the most common cause of death in the UK for women (28% of all female deaths), but not for men, where cancer is now the most common cause of death (32% of all male deaths). Mortality from CVD varies widely throughout the UK, with the highest age-standardised CVD death rates in Scotland (347/100 000) and the North of England (320/100 000 in the North West). Prevalence of coronary heart disease is also highest in the North of England (4.5% in the North East) and Scotland (4.3%). Overall, around three times as many men have had a myocardial infarction compared with women. Treatment for CVD is increasing over time, with prescriptions and operations for CVD having substantially increased over the last two decades. The National Health Service in England spent around £6.8 billion on CVD in 2012/2013, the majority of which came from spending on secondary care. Despite significant declines in mortality in the UK, CVD remains a considerable burden, both in terms of health and costs. Both primary and secondary prevention measures are necessary to reduce both the burden of CVD and inequalities in CVD mortality and prevalence.